2018
DOI: 10.1007/s40134-018-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI for Treatment Evaluation in Patients with Head and Neck Squamous Cell Carcinoma: A Review of the Literature from a Radiologist Perspective

Abstract: Purpose of reviewTo show the role of functional MRI in patients treated for head and neck squamous cell carcinoma.Recent findingsMRI is commonly used for treatment evaluation in patients with head and neck tumors. However, anatomical MRI has its limits in differentiating between post-treatment effects and tumor recurrence. Recent studies showed promising results of functional MRI for response evaluation.SummaryThis review analyzes possibilities and limitations of functional MRI sequences separately to obtain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…However, the readers were skeptical about focal mucosal nonmass and deep ill-defined enhancement patterns. In a previous study, Nooij et al reported that the most controversy for the primary site occurs when both the recurrent tumor and the treatment-induced inflammation show a high T2 signal and postcontrast enhancement [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, the readers were skeptical about focal mucosal nonmass and deep ill-defined enhancement patterns. In a previous study, Nooij et al reported that the most controversy for the primary site occurs when both the recurrent tumor and the treatment-induced inflammation show a high T2 signal and postcontrast enhancement [11].…”
Section: Discussionmentioning
confidence: 99%
“…after surgery and/or radiation therapy) that may obscure viable tumour tissue or mimic disease, and usually cannot provide per se any insight about prognosis, likelihood of early and/or sustained treatment response, or eligibility to patient-tailored target therapies. 14,18–20 On the other hand, both standard CT and MRI data and those derived from more complex implementations of cross-sectional imaging can be joined to build specific radiomic signatures that can lead to improved patient stratification and potentially more personalised treatment 8,21 ( Table 1 ). In this latter setting, a recent large multicentre study by Leijenaar et al combining 902 radiomic features from 778 patients with oropharyngeal SCC showed that CT-based radiomics can predict HPV+ (p16) status from multivariable models obtained from standard pre-treatment CT images.…”
Section: Oropharyngeal Cancermentioning
confidence: 99%
“…This allows overcoming potential confounding factors such as diffuse oedema and contrast enhancement as a result of inflammation and/or post-radiation sequelae, or faint or no enhancement in poorly vascularised and/or highly necrotic tumours, resulting in increased sensitivity in detection of primary oropharyngeal SCC. 14,20 In a recent large meta-analysis, DWI-based apparent diffusion coefficient (ADC) quantitative assessment outperformed anatomical MRI for detection of primary tumour site with a pooled sensitivity and specificity of 89% and 86% vs 84% and 82%, respectively. 20 Lower ADC values have also been found in malignant than in benign lymph nodes sized down to 5–10 mm, and Holzapfel et al were able to correctly classify cervical lymph nodes as benign or malignant using an ADC threshold of 1.02 × 10 −3 mm 2 /s in 94.3% of cases.…”
Section: Oropharyngeal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of imaging diagnosis in identifying and characterizing cervical lymph nodes is undeniable, especially in tumor staging, in which it influences decisions related to the initiation, adjustment, or discontinuation of treatment ( 1 ) . The limitations of conventional magnetic resonance imaging (MRI) for the differentiation between benign and malignant involvement are also recognized, because a reactive lymph node can be enlarged in the same way as a metastatic lymph node, and a normal-sized lymph node can be malignant ( 2 ) . Functional MRI techniques are increasingly used to aid in that differentiation.…”
mentioning
confidence: 99%